2015
DOI: 10.18553/jmcp.2015.21.4.308
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Patterns, Health Care Resource Utilization, and Costs in U.S. Patients Diagnosed with Chronic Hepatitis C Infection Who Received Telaprevir or Boceprevir

Abstract: BACKGROUND: Chronic hepatitis C (CHC) is associated with substantial morbidity and mortality, with the future burden of disease predicted to significantly increase. The recent addition of 2 direct-acting antiviral (DAA) protease inhibitors, telaprevir and boceprevir, to peginterferon alfa (PEG) and ribavirin (RBV) therapy has been shown to significantly improve sustained virologic response rates and thus has become standard of care. While the efficacy and safety of DAAs has been assessed in the clinical trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Regarding the results of our chart review, numerous studies in other countries have demonstrated similar findings, with antiviral drugs accounting for the majority of treatment costs 13,15,27–29. However, they estimate that antiviral costs would amount to around 75–85% of total costs, which is lower than our calculation of 92%.…”
Section: Discussionsupporting
confidence: 79%
“…Regarding the results of our chart review, numerous studies in other countries have demonstrated similar findings, with antiviral drugs accounting for the majority of treatment costs 13,15,27–29. However, they estimate that antiviral costs would amount to around 75–85% of total costs, which is lower than our calculation of 92%.…”
Section: Discussionsupporting
confidence: 79%
“…This may have resulted in larger denominators for the PDC calculation and underestimated the adherence rates. In contrast to the protease inhibitor-based regimens, 24 the high adherence to SOF-based regimens may be attributable to their greater tolerability.…”
Section: Discussionmentioning
confidence: 99%
“…Patients by Adherence Level (adherent) were noted in 60% of patients receiving PEG-IFN with RBV, 46% on PEG-IFN alone, and only 36% of patients taking nonpegylated IFN plus RBV in 1 study; another analysis reported incomplete therapy rates of 74% for BOC and 54% for TVR. 28,37 Several factors may explain these differences, including differing definitions and calculations for adherence, varied follow-up periods, and greater clinical oversight associated with prospective studies and the Veterans Affairs health care program. Treatment discontinuation rates for newer DAAs appear to be much lower (1%-2%) than older therapies, possibly because of better tolerability and oral dosing.…”
Section: Risk Of Liver Transplant In Treatedmentioning
confidence: 99%